2021
DOI: 10.21203/rs.3.rs-435549/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Associated With Death in Confirmed Cases of COVID-19 in the State of Rio De Janeiro

Abstract: Background: We analyzed the factors associated with death in confirmed cases of COVID-19 in the state of Rio de Janeiro. This cross-sectional study evaluated the association between individual demographic, clinical, and epidemiological variables and the outcome (death) using data from the Unified Health System information systems.Methods: We used the extreme boosting gradient (XGBoost) model to analyze the data, which uses decision trees weighted by the estimation difficulty. To evaluate the relevance of each … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Dyspnea, polypnea, chest pain, myalgia, arthralgia, fever, and chills were also the most frequent symptoms. In agreement with those results, dyspnea and fever were also reported by Aktar and Cini Oliveira [25,26]. However, our results indicate that headache, odynophagia, and cough failed to contribute to lethality.…”
Section: Symptoms As Risk Markerssupporting
confidence: 93%
See 1 more Smart Citation
“…Dyspnea, polypnea, chest pain, myalgia, arthralgia, fever, and chills were also the most frequent symptoms. In agreement with those results, dyspnea and fever were also reported by Aktar and Cini Oliveira [25,26]. However, our results indicate that headache, odynophagia, and cough failed to contribute to lethality.…”
Section: Symptoms As Risk Markerssupporting
confidence: 93%
“…Several diagnostic and prognostic models have been proposed for COVID-19, for instance the studies carried out by Aktar et al [ 25 ] and Cini Oliveira et al [ 26 ]. Both approaches evaluated several machine learning models to identify the best predictors of COVID-19 mortality based on demographic data, symptoms and signs, and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…32 Some authors 3 reported that the spatial clusters of social vulnerability were signi cantly associated with increased mortality rates due to COVID-19 and that a higher proportion of African Americans in Chicago had high levels of social vulnerability and several risk factors. At the individual level, Black 33 and non-White people have a higher risk of mortality. 34 Regarding the spatio-temporal progression of the three outcomes, the north region consistently showed a higher excess risk for COVID-19 incidence and mortality during the entire study period.…”
Section: Discussionmentioning
confidence: 99%